Meningkatkan Kualitas Pendidikan melalui Pengelolaan Berkualitas: Pelatihan Manajemen di Madrasah Miftahul Hidayah Bulay (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The quality of madrasah education is strongly influenced by the effectiveness of institutional management. Madrasah Miftahul Hidayah Bulay, as an Islamic educational institution, faces challenges in management practices that have an impact on educational quality. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to improve educational quality through madrasah management training based on Participatory Action Research (PAR). The PAR approach was implemented by actively involving the head of the madrasah, teachers, and educational staff in all stages of the program, including problem identification, action planning, training implementation, and reflection and evaluation. The methods used included observation, focus group discussions, participatory lectures, and case studies. The results indicate an improvement in participants’ managerial understanding and skills, particularly in program planning, task organization, leadership, and evaluation of madrasah management. In addition, the training encouraged the development of a more collaborative and well-directed work culture. Therefore, PAR-based madrasah management training has proven effective in strengthening institutional governance and contributing to the sustainable improvement of educational quality at Madrasah Miftahul Hidayah Bulay.